2006
DOI: 10.1385/mo:23:2:251
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Tropisetron versus Rescue Tropisetron in Fractionated Radiotherapy to Moderate or High Emetogenic Areas: A Prospective Randomized Open Label Study in Cancer Patients

Abstract: Higher numbers of patients receiving prophylactic tropisetron completed RT with lower incidence of nausea and vomiting than those in the rescue tropisetron group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Maranzano et al [31] divided the emetic risk into four levels; high risk (>90%) in total body irradiation, moderate risk (60-90%) in upper abdomen, low risk (30-59%) in lower thoracic and pelvic region and minimal risk (<30%) in cranium, breast, extremities and head and neck field. Our study, as well as those from IGARR [25] and Mystakidou et al [36] may suggest that the thoracic and pelvic fields should be classified as producing moderate risk instead of low risk and head, neck or brain field should be classified as low risk instead of minimal risk for nausea.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Maranzano et al [31] divided the emetic risk into four levels; high risk (>90%) in total body irradiation, moderate risk (60-90%) in upper abdomen, low risk (30-59%) in lower thoracic and pelvic region and minimal risk (<30%) in cranium, breast, extremities and head and neck field. Our study, as well as those from IGARR [25] and Mystakidou et al [36] may suggest that the thoracic and pelvic fields should be classified as producing moderate risk instead of low risk and head, neck or brain field should be classified as low risk instead of minimal risk for nausea.…”
Section: Discussionsupporting
confidence: 74%
“…A combined treatment with a 5-HT 3 antagonist and corticosteroids given as prophylaxis had additional effects compared to a 5-HT 3 antagonist combined with placebo (77% versus 88% experienced nausea or vomiting) [37]. 5HT 3 -receptor antagonists given prophylactic (50% had nausea) was more effective than 5HT 3 -receptor antagonists rescue (65% had nausea) [36]. There are differences between the antiemetic guidelines regarding when and how 5-HT 3 antagonists should be prescribed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of antiemetics given on an as-needed basis has been investigated in three randomized trials [24,30,32].…”
Section: Rescue Therapymentioning
confidence: 99%
“…In the latest study including 288 patients, the value of prophylactic versus rescue tropisetron was evaluated in fractionated radiotherapy of moderate or high emetogenic radiation fields [32]. Although no stratification in regard of radiation fields were conducted, it can be concluded that prophylactic tropisetron was superior over rescue tropisetron in regard to vomiting (risk 2.19 higher for rescue, p= 0.001) and nausea (risk 1.89 higher for rescue, p=0.009).…”
Section: Rescue Therapymentioning
confidence: 99%